Re-Founding The World : a Western Testament. - Guillebaud, Jean-Claude (Algora Pub., 2007)
"[A leading French Christian writer,] Guillebaud leads the search for the Greek, Jewish and Christian roots of our fundamental Western values. . . an erudite and frank analysis of the perverse trends that undermine morality today and calls for a revolutio.